Rheumatic Heart Disease in East of Bali Indonesia - Trisna Ardani, Nyoman Intan; Gede Aditya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Rheumatic heart disease remains to be the most acquired heart disease among people aged <25 years. Despite improvements in high sociodemographic countries, low and low-middle sociodemographic countries have been less successful in lowering the burden of RHD.1 However, data of patient with RHD is still lacking in Indonesia, especially in Bali. Karangasem is a rural area, one of the regencies in the eastern part of Bali. Methods: This retrospective study was performed between January 2023 and January 2024 at two hospitals in Karangasem Regency, Karangasem Regional General Hospital and BaliMed Karangasem Hospital. These two hospitals were the only hospital in Karangasem regency. The study population comprised all patients who were diagnosed with RHD. Patient characteristics and echocardiographic parameters were collected retrospectively from medical records. Results: Data from 101 patients with RHD were collected. They were predominantly female (73.3%) young adults (mean ages 41.97 years), graduated from primary school (58.4%), unemployed (26.7%), and mostly from the Karangasem subdistrict (34.7%). Mitral stenosis and mitral regurgitation were the same counts (65.3%), with mixed valve lesions (mitral and aortic) as the most common lesion (45.5%). Fifty-eight patients (57.4%) had secondary tricuspid regurgitation, with 6 patients with TR V-Max >3.4m/s. Atrial fibrillation was a common complication (47.5%). Most patient with RHD had preserved Left Ventricular Ejection Fraction (LVEF >50%). Only a quarter of patients had reduced RV contractility (TAPSE <17mm). All of the patients with AF were given warfarin. All under 40-year-old patients were given a benzathine penicillin G injection. Only 7 patients had a history of valve surgery. Conclusion: Mixed valve lesion (mitral and aortic) was the most observed condition of valve lesion in RHD with the same count of mitral stenosis and mitral regurgitation. Characteristic of patients in this study were predominantly female, young adult, graduated from primary school, unemployed, had preserved LV function, normal RV contractility, high prevalence of AF with all prescribed warfarin, all of under 40 years were given antibiotics prophylaxis.